Metabolomics profiles revealed potential biomarkers of Pacific white shrimp (Litopenaeus vannamei) under cold and low salinity stress - Zhenzhu Sun; Pei Lin; Haobin Mai; Leling Chen; Zonglu Wei; Beiping Tan; Chaoxia Ye (Aquaculture Reports)
Temperature and salinity are the most important environmental factors in the culture of Pacific white shrimp (Litopenaeus vannamei). This study aimed to investigate the effects of long-term low temperature and low salinity stress on the hepatopancreas metabolome of L. vannamei. A two-factor experiment of temperature and salinity was designed with four treatments, namely HSHT (20psu, 28 °C), HSLT (20psu, 20 °C), LSHT (5psu, 28 °C), and LSLT (5psu, 20 °C). Results showed that weight gain ratio was significantly inhibited by low temperature but less affected by low salinity. LC-MS analysis revealed overlapping significant pathways, including ABC transporters, protein digestion, aminoacyl-tRNA biosynthesis, purine metabolism, and pyrimidine metabolism, with an additional pathway (mineral absorption) in the salinity change group. Moreover, seven metabolites were significantly involved during cold or salinity stress. Notably, dihydrothymine and stachyose may serve as biomarkers for measuring cold stress, while phosphorylcholine may indicate salinity stress levels. This study highlights the metabolic regulation of L. vannamei in response to low temperature and salinity, offering valuable insights into their domestication under cold and low-salt conditions.